2019
DOI: 10.1123/jmld.2018-0055
|View full text |Cite
|
Sign up to set email alerts
|

Single-Leg Balance Performance in Sub-Elite Young Soccer Players and Swimmers as a Function of Age and Sports Experience

Abstract: The present study investigated if accumulated, advanced, regular soccer practice (balance-demanding exercise) compared to regular swim practice (non-balance–demanding exercise) induces a more pronounced functional specialization in postural control. Therefore, single-leg balance performance in sub-elite young soccer players (under 13 [U13]: n = 16; U15: n = 18; U19: n = 15), and sub-elite young swimmers (U13: n = 7; U15: n = 4; U19: n = 5) was tested in different balance task conditions (i.e., static and dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…A power analysis conducted with G*Power (version 3.1;Faul et al, 2007) using the power of 80% and the effect size from the between-subject main effect age of the Muehlbauer et al (2019) experiment and an effect size of ƒ = 0.40 indicated that the inclusion of 64 athletes as a total sample size was sufficient to detect an effect of age with the YBT-LQ test for the anterior reach asymmetry of ≥4 cm. As far as we know, previous studies used age instead of training experience as a grouping variable (e.g., Leinen et al, 2019;Muehlbauer et al, 2019;Paillard, 2017). Therefore, the calculated sample size seems to be a good estimate.…”
Section: Participantsmentioning
confidence: 93%
See 1 more Smart Citation
“…A power analysis conducted with G*Power (version 3.1;Faul et al, 2007) using the power of 80% and the effect size from the between-subject main effect age of the Muehlbauer et al (2019) experiment and an effect size of ƒ = 0.40 indicated that the inclusion of 64 athletes as a total sample size was sufficient to detect an effect of age with the YBT-LQ test for the anterior reach asymmetry of ≥4 cm. As far as we know, previous studies used age instead of training experience as a grouping variable (e.g., Leinen et al, 2019;Muehlbauer et al, 2019;Paillard, 2017). Therefore, the calculated sample size seems to be a good estimate.…”
Section: Participantsmentioning
confidence: 93%
“…In soccer, successful performance requires a pronounced single-leg balance capability, that is, the nondominant leg is responsible for stabilization, whereas the dominant leg is related to kicking and passing the ball (e.g., Chew-Bullock et al, 2012;Hart & Gabbard, 1997;Leinen et al, 2019;Matsuda et al, 2008;Teixeira et al, 2011). Due to the balance demands in soccer and the theoretical account of the functional specialization of the neuromuscular system (Paillard, 2017), the asymmetry in balance performance can be an accompanying symptom for an increased risk to sustain injuries to the lower extremities (Muehlbauer et al, 2019).…”
mentioning
confidence: 99%
“…The inner foot was placed on the left marker when the left foot was the stance foot, and on the right marker when the right foot was the stance foot. As in the Leinen et al (2019) protocol, tasks 1 to 4 represent the static and tasks 5 to 8 the dynamic balance tasks, respectively. The four static balance tasks included the single-leg stance with the right and left leg on firm and foam ground.…”
Section: Apparatus and Tasksmentioning
confidence: 99%
“…For example, to determine performance asymmetry in leg stability, single-leg balance performance is evaluated. In some studies, balance performance was compared between the dominant and non-dominant leg of children, young adults, and adolescents (e.g., Leinen, Muehlbauer, & Panzer, 2019;Muehlbauer, Schwiertz, Brueckner, Kiss, & Panzer, 2019;Snyder & Cinelli, 2020;Teixeira & Teixeira, 2008) without consideration of analyzing anthropometric parameters. Young adult individuals are especially characterized by large inter-individual differences in their anthropometric characteristics resulting in accelerated and retarded performers (Musch & Grondin, 2001).…”
mentioning
confidence: 99%
“…Paillard [ 20 ], in a review on the role of balance in sports performance, found that the practice of physical exercise could induce structural and functional adaptations in the postural control system. Nevertheless, previous studies have found differences in balance performance between athletes of different sports modalities, suggesting that only certain sports would benefit from the development of this skill among their practitioners [ 21 ]. This is the case of gymnasts, whose performance is based on the execution of different technical skills that require great postural mastery, both in static and dynamic situations [ 15 ].…”
Section: Introductionmentioning
confidence: 99%